IMPACT OF COVID-19 PANDEMIC ON AIR QUALITY IN URBAN AND SUBURBAN AREAS IN INDONESIA - Meliana Qatrunnada, Khalisha
In April 2020, the first social restrictions were imposed by the Indonesian government to prevent the spread of COVID-19. Since it restricts human mobility, it may improve the air quality. This study was conducted to determine the effect by comparing the concentration of air pollutants and aerosol characteristics during the Large-Scale Social Restriction (PSBB) period and when the peak of the Delta variant of COVID-19 cases occurred in urban areas (Central Jakarta and Bandung) and suburban areas (Palangka Raya and Jambi). We obtained daily data on pollutant concentrations from air quality monitoring stations (AQMS) and aerosol characteristics from the Aerosol Robotic Network (AERONET). The aerosol characteristics data includes aerosol optical depth (AOD), Angstrom exponent (AE), and volume size distribution. To determine the significance of the changes, the Mann-Whitney U and t-test were used. There was no significant decrease in air pollutant concentrations during the PSBB period. A significant decrease in AOD was found in Bandung (-36.3%) and Jambi (-35.7%). Meanwhile, during the peak period of COVID-19, only Bandung experienced a significant decrease in pollutant concentrations of 17.7%, 43.4%, and 30.1% for the CO, NO2, and SO2 parameters, respectively. Based on the AOD value, only Central Jakarta experienced a significant drop, which was 6.1%. The average value of AE was found to be greater than 1.00 in each study site and period.